TANGGAPAN SISWA TERHADAP PEMBELAJARAN MENULIS TEKS DESKRIPTIF SECARA DARING DENGAN BERBANTUAN GOOGLE CLASSROOM - Anita Nurfitriany; Ika Mustika; Alfa Mitri Suhara (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research is motivated by the difficulties experienced by students in writing descriptive texts. Meanwhile, the State of Indonesia was exposed to the coronavirus, which affected all sectors and one of them was Education. So learning is required online to prevent the transmission of the virus. Google Classroom is a free web service from Google to provide online learning. Google Classroom can be used for teachers and students using mobile phones or laptops wherever they are. This study used the descriptive qualitative method. Data collection techniques in this study were interviews and questionnaires. The sample that the writer examines is class VIII with a total of 22 students. According to the data obtained, learning to write descriptive text online with the help of Google Classroom can motivate students, can reduce the time to understand the material and they dare to express opinions.